Ecolexicon Ke-nila-an - Telaumbanua, Thomas Alfa Edison (e-Journal of Linguistics; Vol 18 No 2 (2024): ejl-JulyDO - 10.24843/e-jl.2024.v18.i02.p04, 2024)
The extinction of a language is a challenge for academics, especially those who focus on the field of linguistics. Several factors in the extinction of a language are the influence of globalization, majority and minority ethnic groups, the young generation's low interest in ancestral culture, and intermarriage. One solution to prevent this is to increase linguistic studies on linguistic lexicons that are related to culture, objects or flora and fauna that were once part of the livelihood of an area but have disappeared because they have disappeared. This research was conducted with the aim of explaining the Ecolexicon ke-nila-an ( Nilam/Patchouli) in the Nias language and the classification of the ecolexicon based on grammatical form. This research uses descriptive qualitative analysis methods. The research data used is primary data obtained through interviews and documentation. Analysis of research data shows that there are 39 ecolexicons found in adjectives, followed by 28 nouns, 9 verbs and 2 adjectives.